Discontinuation of Lamivudine Treatment in HBeAg-Negative Chronic Hepatitis B: A Pilot Study with Long-Term follow-up. Issue 7 (October 2017) - Karakaya, Fatih; Özer, Sevil; Kalkan, Çağdaş; Tüzün, E Ali; Çalişkan, Aysun; Keskin, Onur; Kabaçam, Gökhan; Karatayli, Senem; Karatayli, Ersin; Bozdayi, A Mithat; Idilman, Ramazan; Yurdaydin, Cihan
Background: Finite treatment of hepatitis B e antigen (HBeAg)-negative chronic hepatitis B (CHB) with nucleoside/nucleotide analogues (NAs) is important in resource-limited countries. Outcome of treatment discontinuation in patients on long-term lamivudine (LVD) was assessed in a single centre observational pilot study in the current study. Methods: Non-cirrhotic patients on LVD for at least 5 years with undetectable HBV DNA on at least two consecutive assessments were offered to stop treatment. Biochemical, serological and virological measures were determined at 3–6 month intervals after treatment discontinuation. Serum quantitative hepatitis B surface antigen (HBsAg) was determined at treatment discontinuation and 5–6 years thereafter. NA treatment was re-instituted in patients with confirmed viral rebound defined as HBV DNA >20, 000 IU/ml. Relapser patients were no longer followed but were re-assessed 6 years after treatment cessation. Results: LVD was discontinued in 23 patients. 8 patients relapsed within 1 year and NA treatment was restarted; 15 patients (65%) were non-relapsers. Thirteen of them were followed for at least 5 years. Two patients had undetectable HBV DNA throughout the follow-up period. In the rest, HBV DNA fluctuated at low levels. Two patients cleared HBsAg 24 and 36 months after stopping treatment. Quantitative HBsAg levels 5–7 years after treatment discontinuation were lower in non-relapser compared to relapser patients (1.21 IU/ml ±0.98 versus 2.71 ±0.76; P =0.002). Of 8 relapser patients 1 patient had HBsAg levels less than 100 IU/ml compared to 11 out of 13 non-relapser patients ( P =0.0022). Conclusions: These data suggest that cessation of NA treatment is a viable option after a reasonable treatment duration in patients with HBeAg-negative CHB and that HBsAg clearance may become an achievable target in these patients.